Introducing Chabani Manganyi’s “Making strange” - Hayes, Grahame (PINS-Psychology in Society, 2018)
Chabani Manganyi’s little known article, “Making strange: Race science and ethnopsychiatric discourse”, doesn’t need an introduction as it is quite capable of speaking for itself. And while originally written in 1984, it is still able to speak to us about the important contemporary concerns of race (science), (African) identity, the postcolonial, and even the politics of de-colonisation. Manganyi’s article was first presented at the University of Essex’s conference on the “Sociology of literature” in July 1984. He then presented it again on his return to South Africa at the University of the Witwatersrand’s African Studies Institute in October 1984. It was published in 1985 as part of the conference proceedings by the University of Essex. This somewhat obscure publishing history has given the paper a samizdat quality, being passed from reader to reader in its African Studies Institute’s photocopied version! Even Chabani Manganyi himself doesn’t have a copy of this article (Hook, 2018).